THE ROLE OF INDEPENDENT BOARD OF COMMISSIONERS: A STUDY OWNERSHIP ON ESG DISCLOSURE: ESG Disclosure - Susanto, Ari; Novita, Novita; Fambudi, Imam Nurcahyo (Faculty of Economics and Business University of Mataram, 2024)
This study aims to examine the impact of stakeholder involvement, namely foreign and institutional ownership, on ESG disclosure and how the relationship is moderated by the independent board of commissioners. This study uses a sample of 108 manufacturing companies listed on the IDX during the 2019-2021 period. Data analysis was carried out using the Ordinary Least Square (OLS) method using a random effect model. The results showed that foreign ownership, institutional ownership, and independent boards of commissioners have a positive influence on ESG disclosure. In addition, an independent board of commissioners is proven to strengthen the effect of institutional ownership on ESG disclosure. In contrast, company size as a control variable has no impact on ESG disclosure. This study suggests companies in the manufacturing sub-sector increase ESG disclosure, which can be encouraged through the presence of foreign and institutional ownership.